Effectiveness of the ELSA Application in Enhancing English Pronunciation in Inclusive Education - Dewi Untari; Setyorini Dwi Agustini; Siti Yuliana (INCARE, International Journal of Educational Resources, 2026)
The development of digital technology has driven a transformation toward more interactive and adaptive learning. However, vocational high school students, particularly in inclusive schools, still face challenges in English pronunciation skills. The main problem addressed in this study is the limited use of instructional media and the diverse characteristics of students, including those with special educational needs, which affect the learning process. This study aims to (1) describe the implementation of the ELSA (English Language Speech Assistant) application in English learning and (2) analyze its effect on improving students’ pronunciation skills at SMK Inklusi TPA Jember. This research employed Classroom Action Research (CAR) conducted in two cycles, consisting of planning, action, observation, and reflection stages. Data were collected through pre-test and post-test, as well as observations and interviews. The results showed a gradual improvement in students’ average scores, from 62.3 in the pre-test to 71.0 in the first cycle post-test (an increase of 8.7 points or 14.0%), and further to 81.5 in the second cycle post-test (a total increase of 19.2 points or 30.8%), shifting from low to moderate and finally to good categories. Qualitative analysis revealed clear improvements from cycle I to cycle II, indicated by changes in student engagement from passive to active and independent, as well as more responsive and exploratory behavior toward practice and feedback. In addition, students’ pronunciation became more accurate and structured, indicating that the use of the ELSA application is effective in enhancing both the process and outcomes of pronunciation learning.